THE IMPORTANCE OF ALISHER NAVOI'S CREATIVE HERITAGE IN THE FORMATION OF MUSICAL THINKING OF STUDENT YOUTH - Sharipova Odinahon Shavkatjon Daughter; Hasanboeva Shahlo Shermurod Daughter (Journals Park Publishing, 2022)
This article discusses the contribution of the famous poet Alisher Navoi to the development of music science, as well as the importance of music science in his works and the importance of musical thinking in the formation of the spiritual image of young people.